2021
DOI: 10.1155/2021/6664386
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Molecular Characterization in Hepatocellular Carcinoma Identifies One Risk Signature and Two Nomograms for Clinical Management

Abstract: Hypoxia is a universal feature in the tumor microenvironment (TME). Nonetheless, the heterogeneous hypoxia patterns of TME have still not been elucidated in hepatocellular carcinoma (HCC). Using consensus clustering algorithm and public datasets, we identified heterogeneous hypoxia subtypes. We also revealed the specific biological and clinical characteristics via bioinformatic methods. The principal component analysis algorithm was employed to develop a hypoxia-associated risk score (HARS). We identified the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 55 publications
1
32
0
Order By: Relevance
“…While ICIs target the interactions between immune and tumour cells within the TME, certain alterations that occur in the TME can also affect the responsiveness to immunotherapy 3 . Recent studies have confirmed that key biological processes such as autophagy, hypoxia and ferroptosis, as well as some molecular alterations, can contribute to the immunotherapeutic efficacy and prognosis of cancer patients by affecting the distributions and interactions of distinct immune cell subsets in the TME 10–13 . To date, there are still few cancer patients who can benefit from immunotherapy, and thus, it is essential to explore additional therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…While ICIs target the interactions between immune and tumour cells within the TME, certain alterations that occur in the TME can also affect the responsiveness to immunotherapy 3 . Recent studies have confirmed that key biological processes such as autophagy, hypoxia and ferroptosis, as well as some molecular alterations, can contribute to the immunotherapeutic efficacy and prognosis of cancer patients by affecting the distributions and interactions of distinct immune cell subsets in the TME 10–13 . To date, there are still few cancer patients who can benefit from immunotherapy, and thus, it is essential to explore additional therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“… 37 In one study on primary soft tissue sarcoma, the concurrent application of a hypoxia signature and a signature measuring the degree of genomic instability revealed a significant enrichment of hypoxic tumors in the group classified as having high genomic instability. 38 The positive correlation between hypoxia and TMB has been further validated in independent studies for hepatocellular carcinoma, 39 gastric cancer 40 and pancreatic cancer. 41 In gastric cancer, TMB positivity was further correlated with higher positive rate of ERO1A protein, a marker of hypoxia, in 73 tumors tested by immunohistochemistry.…”
Section: Computational Analysis Of Publicly Available Datasets Links Hypoxia With Tmbmentioning
confidence: 79%
“…Despite the approval of few ICIs and several ongoing clinical trials, ICIs as a monotherapy have failed to show promising result as first-line treatment in HCC compared to Sorafenib 53 , 54 . In addition, the response of HCC patients to ICIs may be affected by several molecular features including genetic alterations, variation in inflammatory infiltrates, microsatellite instability (MSI) and expression of alternative immune checkpoint molecules 53 , 55 , 56 . Thus, there is a need for identification of robust predictive biomarkers along with combined ICI therapeutic approaches for enhanced clinical outcome in HCC patients 53 .…”
Section: Discussionmentioning
confidence: 99%
“…The HCC TME includes cancer cells, immune cells [T-cells, B-cells, dendritic cells, myeloid-derived suppressor cells (MDSCs), tumor-associated macrophages (TAMs)], carcinoma-associated fibroblasts, endothelial cells, hepatic stellate cells, and the extracellular matrix (ECM) 65 . As the TME is a crucial facilitator of HCC progression and resistance to immunotherapies, much of the recent research is focused on the various components of the TME to identify predictive and prognostic biomarkers for ICI treatment in HCC patients 56 , 66 . For instance, a study developed a prognostic biomarker for immunotherapy comprising of eight gene risk signature based on hypoxia status in the TME of HCC patient 56 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation